Surface-treated copper foil for printed wiring board, copper-clad laminate for printed wiring board using the same, and printed wiring board
By forming a specific surface treatment coating on the surface of the copper foil substrate, the problems of adhesion and transmission loss between the copper foil and the resin substrate in the high-frequency band domain are solved, and excellent high-frequency characteristics, heat adhesion and powder drop resistance are achieved.
Patent Information
- Application Number
- CN202180023821.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-27
- Filing Date
- 2021-03-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-03-25
AI Technical Summary
The prior art is difficult to take into account the high adhesion and low transmission losses of copper foil and resin substrate in the high frequency band domain, especially in high temperature environments, and the roughened particles are excessively fine, resulting in powder falling off.
By forming a surface treatment coating containing roughened particles on at least one surface of the copper foil substrate, the mirror gloss and gloss ratio is controlled, so that the surface treatment copper foil has excellent high-frequency characteristics, normal adhesion and heat-resistant adhesion, and reduces powder drop.
It achieves low transmission loss in the high frequency band domain, high bonding and heat bonding resistance, and improves powder drop resistance of surface-treated copper foil.
Smart Images

Figure CN115279951B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a surface-treated copper foil for a printed wiring board used in a high frequency band, particularly in a high frequency band of 1 to 10 GHz. The present invention also relates to a copper-clad laminate for a printed wiring board and a printed wiring board using the surface-treated copper foil for a printed wiring board. Background Art
[0002] In recent years, with the multi-layering of substrates supporting high frequencies, different types of copper foils have begun to be used according to the characteristics required for the inner and outer layers. In particular, the outer layer requires high adhesion, so copper foil with a roughening treatment layer (a layer forming roughening particles) formed on the M (matte) side of the electrolytic copper foil with large unevenness, which is called general foil or general foil, is often used.
[0003] However, in recent years, high-frequency signals with a frequency of 1 to 10 GHz have been flowing even in the outer layer. If the above frequency is reached, the epidermis depth of the current flow reaches about 0.7 to 2.0 μm, and the current flows only in the very surface layer of the conductor. Therefore, when the surface of the conductor is large, the transmission path of the conductor (i.e., the transmission path of the epidermis) becomes longer and the transmission loss increases. Therefore, in the copper-clad laminate used in the device supporting high frequency, in order to suppress the increase of transmission loss, it is desired to reduce the surface unevenness of the copper foil.
[0004] Therefore, copper foil called RTF foil, which is roughened on the S (bright) side of the electrolytic copper foil with smaller irregularities, is often used as an outer layer. It should be noted that there is also copper foil called double-sided glossy foil, which is smooth on both the M side and the S side, but it has excessive transmission characteristics as an outer layer material, is expensive, and has poor adhesion required as an outer layer material, so it is rarely used.
[0005] In addition, usually for copper foil used for printed wiring boards, in addition to transmission characteristics, high adhesion to the resin substrate is also required. Generally speaking, as a means to improve the bonding force between the resin substrate and the copper foil surface, a means of obtaining a physical bonding effect (anchoring effect) with the resin substrate by forming a roughening treatment layer on its surface by electroplating, etching, etc. can be cited. However, in order to effectively improve the adhesion between the copper foil surface and the resin substrate, if the particle size of the roughening particles formed on the copper foil surface is increased, the transmission loss increases as described above.
[0006] As described above, in copper-clad laminates, there is a trade-off between the suppression of transmission loss and the improvement of the adhesion (bonding) between the copper foil and the resin substrate (i.e., the improvement of durability). Therefore, for copper foil used in copper-clad laminates, research has been conducted to balance the suppression of transmission loss and the adhesion with the resin substrate.
[0007] Therefore, printed wiring boards that support high frequencies have recently been used in fields that require higher reliability. For example, in printed circuit boards for mobile communication devices such as vehicle-mounted printed circuit boards, high reliability that can withstand harsh environments such as high temperature environments is required. In order to meet such high reliability requirements, it is necessary to further improve the adhesion between copper foil and resin substrates. For example, it is necessary to be able to withstand the rigorous test of a reflow test with a maximum temperature of 260°C repeated 20 times. Therefore, the above-mentioned conventional means cannot meet the adhesion (heat-resistant adhesion) in a harsh high temperature environment required in recent years.
[0008] In addition, for the copper foil for printed wiring board, in order to improve the bonding force with resin base material, except forming the above-mentioned roughening treatment layer, also use by processing the copper foil surface with silane coupling agent, thereby obtain the means of chemical bonding to resin base material. However, between silane coupling agent and resin base material, in order to improve chemical bonding, it is necessary for resin base material to have a certain degree of large substituent with polarity. However, in order to suppress dielectric loss, as resin base material, when using the low dielectric property base material of the amount of the large substituent with polarity reduction, even use silane coupling agent to process the copper foil surface, it is also difficult to obtain chemical bonding, and it is difficult to ensure the sufficient bonding of copper foil and resin base material.
[0009] Therefore, a surface-treated copper foil for a printed wiring board that achieves both high adhesion between the copper foil and the resin substrate and suppression of conduction loss is being studied (for example, see Japanese Patent Gazette No. 6294862 (Patent Document 1)). In the surface-treated copper foil for a printed wiring board described in Patent Document 1, fine concavities and convexities are formed on the surface to increase the specific surface area of the surface, thereby achieving suppression of transmission loss and normal adhesion and heat-resistant adhesion between the copper foil and the resin substrate. Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, in the surface-treated copper foil for printed wiring boards described in Patent Document 1, the roughened particles are too fine, and particularly in the case of an outer layer of a substrate for supporting high frequencies, the normal adhesion and heat-resistant adhesion between the copper foil and the resin substrate are not sufficient. In addition, when the technology for surface-treated copper foil for printed wiring boards described in Patent Document 1 is used to improve the normal adhesion and heat-resistant adhesion between the copper foil and the resin substrate, it is possible that powder may fall off if the roughened particles are only coarsened.
[0012] The object of the present invention is to provide a surface-treated copper foil for a printed wiring board having excellent transmission characteristics in a high-frequency band (hereinafter sometimes referred to as "high-frequency characteristics"), excellent normal adhesion and heat-resistant adhesion to a resin substrate, and resistance to powder falling, as well as a copper-clad laminate for a printed wiring board and a printed wiring board using the same.
[0013] Means for solving problems
[0014] As a result of in-depth research by the inventors to solve the above-mentioned previous problems, it was found that not only laser microscopes and non-contact interference microscopes cannot be defined, but also complex roughening shapes cannot be defined even by SEM. In addition, the shape can be evaluated by the glossiness measured from a specified angle and the glossiness ratio between the glossiness measured from two specified angles. If the glossiness and the glossiness ratio are within the specified numerical range, a surface-treated copper foil for a printed wiring board having excellent transmission characteristics in a high-frequency band, excellent normal adhesion and heat-resistant adhesion with a resin substrate, and excellent resistance to powder falling is obtained, thereby completing the present invention.
[0015] That is, the gist of the present invention is as follows.
[0016] [1] A surface-treated copper foil for a printed wiring board, comprising a surface-treated film including a roughening-treated layer formed with roughening particles on at least one surface of a copper foil substrate, wherein the surface of the surface-treated film has a 20-degree specular gloss Gs(20°) in TD measured in accordance with JIS Z8741:1997 of less than 0.8%, a 60-degree specular gloss Gs(60°) in TD measured in accordance with JIS Z 8741:1997 of 0.4% or more, and a specular gloss ratio (Gs(45°) / Gs(75°)) of a 45-degree specular gloss Gs(45°) in TD measured in accordance with JIS Z 8741:1997 of the surface of the surface-treated film of not less than 0.1 and not more than 1.5.
[0017] [2] The surface-treated copper foil for a printed wiring board according to [1] above, wherein the surface of the surface-treated coating has a TD 85-degree specular glossiness Gs (85°) of 4% or more and less than 50% as measured in accordance with JIS Z 8741:1997.
[0018] [3] The surface-treated copper foil for a printed wiring board according to [1] or [2], wherein the surface of the copper foil substrate having the surface-treated coating is a glossy surface.
[0019] [4] The surface-treated copper foil for a printed wiring board according to any one of [1] to [3], wherein the Y value of the surface of the surface-treated coating in the XYZ chromaticity system of TD measured in accordance with JIS Z 8781 is 10% or more and 45% or less.
[0020] [5] The surface-treated copper foil for a printed wiring board according to any one of [1] to [4], wherein the surface of the surface-treated coating has a ten-point average roughness Rzjis value of 0.8 μm or more and 4.5 μm or less as measured in accordance with JIS B 0601.
[0021] [6] A copper-clad laminate for a printed wiring board, obtained by bonding the surface of the surface-treated copper foil for a printed wiring board according to any one of [1] to [5], on which the surface-treated coating is formed, to a resin substrate.
[0022] [7] A printed wiring board comprising the copper-clad laminate for a printed wiring board according to [6] above.
[0023] Effects of the Invention
[0024] According to the present invention, it is possible to provide a surface-treated copper foil for a printed wiring board having excellent transmission characteristics in a high-frequency band, excellent normal adhesion and heat-resistant adhesion to a resin substrate, and excellent resistance to powder falling, as well as a copper-clad laminate for a printed wiring board and a printed wiring board using the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a diagram for explaining the state of roughened particles in the surface-treated copper foil of the present invention.
[0026] Figure 2 This is a diagram for explaining the state of roughened particles in a conventional surface-treated copper foil.
[0027] Figure 3 This is a schematic diagram of an apparatus for manufacturing electrolytic copper foil.
[0028] Figure 4 This is an example of a SEM image obtained by observing the surface of the surface-treated film of the surface-treated copper foil of the present invention from a processed cross section. DETAILED DESCRIPTION
[0029] Hereinafter, preferred embodiments of the surface-treated copper foil for a printed wiring board of the present invention will be described in detail. In addition, the expression of the numerical range of "AA to BB" in this specification means "AA or more and BB or less".
[0030] The surface-treated copper foil for a printed wiring board of the present invention (hereinafter sometimes referred to as "surface-treated copper foil") comprises a surface-treated coating including a roughening-treated layer having roughening particles formed thereon on at least one surface of a copper foil substrate, wherein the surface of the surface-treated coating has a 20-degree specular gloss Gs(20°) in TD measured in accordance with JIS Z 8741:1997 of less than 0.8%, a 60-degree specular gloss Gs(60°) in TD measured in accordance with JIS Z 8741:1997 of 0.4% or more, and a specular gloss ratio (Gs(45°) / Gs(75°)) of a 45-degree specular gloss Gs(45°) in TD measured in accordance with JIS Z 8741:1997 of the surface of the surface-treated coating of 0.1 or more and 1.5 or less. It should be noted that TD (Transverse Direction) is a direction perpendicular to the direction in which the copper foil substrate flows when the copper foil substrate is manufactured (sometimes also referred to as MD (Machine Direction), RD (Roll Direction)). That is, the "specular glossiness" in the present invention refers to the glossiness when light is incident from the TD direction (a direction perpendicular to the MD direction).
[0031] The surface-treated copper foil of the present invention has a surface-treated coating including a roughening treatment layer on at least one surface of a copper foil substrate. The roughening treatment layer is formed with roughening particles. The surface of the surface-treated coating is at least one of the outermost surfaces (front and back surfaces) of the surface-treated copper foil, and is a roughened surface having a complex concave-convex surface shape reflecting the formation state and particle shape of the roughening particles, etc., formed on at least one surface of the copper foil substrate.
[0032] The surface of such a surface-treated film (hereinafter referred to as "roughened surface") may be, for example, the surface of a roughened layer formed on a copper foil substrate, or the surface of a silane coupling agent layer formed directly on the roughened layer, or the surface of a silane coupling agent layer formed on the roughened layer via an intermediate layer such as a base layer containing Ni, a heat-resistant layer containing Zn, and a rust-proof layer containing Cr. In addition, when the surface-treated copper foil of the present invention is used for a conductor loop of a printed wiring board, the roughened surface becomes a surface (bonding surface) for bonding a laminated resin substrate.
[0033] Here, an example of a schematic cross-sectional view of the roughened surface of the surface-treated copper foil of the present invention is shown in Figure 1 An example of a schematic cross-sectional view of a roughened surface of a conventional surface-treated copper foil is shown in Figure 2 .like Figure 1As shown in FIG. 1 , the roughened surface of the surface-treated copper foil of the present invention has roughened particles precipitated in a dendrite-like manner and having a complex concavoconvex surface. Figure 2 As shown, the surfaces of the roughened particles of the conventional surface-treated copper foil do not have complex irregularities like the surfaces of the roughened particles of the surface-treated copper foil of the present invention.
[0034] For the shape evaluation of the roughened particles in the special roughened surface such as the surface-treated copper foil of the present invention, the conventional means of observing the roughened surface, such as laser microscope, white interference microscope, etc., is to observe from the vertical direction of the roughened surface, and cannot correctly display the characteristics of the roughened particles with a surface having complex concavoconvex surfaces. In addition, even in direct two-dimensional shape observation such as cross-sectional observation using SEM, it is difficult to correctly define the three-dimensional characteristics of the roughened particles with a surface having complex concavoconvex surfaces. Therefore, the conventional means have limitations in the strict evaluation of the roughened surface at the technical level. Therefore, in the present invention, as a means of evaluating the roughened surface, the characteristics of the roughened surface are defined by the mirror gloss measured according to JIS Z8741:1997, so as to evaluate it. Specifically, it is carried out by the following means.
[0035] Usually, the measurement of specular glossiness is generally measured and evaluated at a single light receiving angle. However, the roughened surface of the surface-treated copper foil of the present invention forms a complex shape by forming roughened particles, so it is difficult to fully evaluate the characteristics of its surface shape at a single light receiving angle. Therefore, for the roughened surface of the surface-treated copper foil of the present invention, the specular glossiness is measured using the following light receiving angles, thereby being able to evaluate the surface shape of the roughened surface.
[0036] It should be noted that, as mentioned above, the measurement of the specular glossiness of the roughened surface is not the measurement on the smooth surface, and therefore the measured values at the following light receiving angles do not have a simple proportional relationship.
[0037] The 20-degree specular gloss Gs(20°) of the surface of the surface-treated coating measured in accordance with JIS Z 8741:1997 is less than 0.8%. If Gs(20°) is 0.8% or more, it is considered that the roughened particles become excessively fine, and there is a tendency for the heat-resistant adhesion between the surface-treated copper foil and the resin substrate to decrease. Furthermore, from the viewpoint of also improving the normal adhesion between the surface-treated copper foil and the resin substrate, Gs(20°) is preferably less than 0.7%, and more preferably less than 0.6%. In addition, Gs(20°) is preferably 0.1% or more. If Gs(20°) is 0.1% or more, the high-frequency characteristics are particularly improved. From such a viewpoint, Gs(20°) is more preferably 0.2% or more, and further preferably 0.3% or more.
[0038] The 60-degree specular gloss Gs(60°) of the surface of the surface-treated coating measured in accordance with JIS Z 8741:1997 in TD is 0.4% or more. If Gs(60°) is less than 0.4%, it is considered that the roughened particles are too large for the purpose of the present invention and the high-frequency characteristics are reduced. From this point of view, Gs(60°) is preferably 0.5% or more. In addition, Gs(60°) is preferably 10.0% or less. If Gs(60°) is 10.0% or less, the heat-resistant adhesion is particularly improved. From this point of view, Gs(60°) is more preferably 6.0% or less, further preferably 1.8% or less, and further preferably 0.9% or less.
[0039] The mirror gloss ratio (Gs(45°) / Gs(75°)) of the 45-degree mirror gloss Gs(45°) to the 75-degree mirror gloss Gs(75°) of the surface of the surface treatment film measured in accordance with JIS Z 8741:1997 is 0.1 or more and 1.5 or less. The magnitude of the mirror gloss ratio (Gs(45°) / Gs(75°)) is considered to indicate the tendency of dendritic precipitation extending obliquely in a direction with a large angle relative to the direction perpendicular to the copper foil substrate. Dendritic precipitation extending in a direction with a large angle relative to the direction perpendicular to the surface of the surface treatment film is considered to provide a physical adhesion effect (anchor effect) when the resin substrate and the surface-treated copper foil are bonded. The specular gloss ratio (Gs(45°) / Gs(75°)) being greater than 1.5 can be considered to mean that the dendritic precipitation from the roots of the roughened particles is excessively formed, and by fully eliminating the strength of the root portion of the roughened particles, the surface-treated copper foil is prone to powder falling, and there is a tendency for the powder falling resistance to be reduced. From this point of view, the specular gloss ratio (Gs(45°) / Gs(75°)) is preferably 1.3 or less, more preferably 1.2 or less, and further preferably 1.0 or less. On the other hand, it is difficult to manufacture the specular gloss ratio (Gs(45°) / Gs(75°)) to be less than 0.1. In addition, it can be considered that the larger the value of the specular gloss ratio (Gs(45°) / Gs(75°)), the greater the ratio of the dendritic precipitation extending in a large angle direction relative to the direction perpendicular to the copper foil substrate, which has a strong influence on the anchoring effect, and there is a tendency for the heat-resistant adhesion of the surface-treated copper foil to the resin substrate to be improved. From such a viewpoint, the mirror gloss ratio (Gs(45°) / Gs(75°)) is preferably 0.5 or more, more preferably 0.7 or more, and further preferably 0.8 or more. More specifically, the mirror gloss ratio (Gs(45°) / Gs(75°)) is preferably 0.5 or more and 1.5 or less, more preferably 0.7 or more and 1.3 or less, further preferably 0.7 or more and 1.2 or less, further preferably 0.7 or more and 1.0 or less, and further preferably 0.8 or more and 1.0 or less, from the viewpoint of improving the resistance to powder falling and the heat-resistant adhesion between the surface-treated copper foil and the resin substrate.
[0040] It should be noted that Gs (45 °) and Gs (75 °) may satisfy the above ranges as the mirror gloss ratio (Gs (45 °) / Gs (75 °)), and as a single value, it may be set to, for example, the following ranges. Gs (45 °) is preferably 5.0 or less, more preferably 0.5 or more and 3.0 or less. In addition, Gs (75 °) is preferably 20.0 or less, more preferably 0.5 or more and 10.0 or less.
[0041] By setting Gs(20°) and Gs(60°) within the above range and setting the mirror gloss ratio (Gs(45°) / Gs(75°)) within the above range, even if the roughened particles are not increased, excellent normal adhesion can be obtained through the physical adhesion effect (anchoring effect), and not only that, excellent heat-resistant adhesion that cannot be expected in the chemical adhesion using a silane coupling agent can be obtained, and the transmission characteristics (high-frequency characteristics) in the high-frequency band of the surface-treated copper foil can be improved. In addition, powder falling can be effectively suppressed.
[0042] Furthermore, the 85-degree specular gloss Gs (85°) of the surface of the surface-treated coating measured in accordance with JIS Z 8741:1997 is preferably 4% or more and less than 50%. Gs (85°) can be considered to reflect the state of dendritic precipitation that extends obliquely in a direction with a large angle relative to the direction perpendicular to the copper foil substrate and has an effect on the anchoring effect. If Gs (85°) is less than 50%, it can be considered that the dendritic precipitation that has a strong effect on the anchoring effect is sufficient, and the heat-resistant adhesion between the surface-treated copper foil and the resin substrate is improved. If Gs (85°) is 4% or more, it can be considered that the dendritic precipitation from the roots of the roughened particles will not be excessive, the surface-treated copper foil is less likely to cause powder falling, and the resistance to powder falling is improved. From this viewpoint, Gs (85°) is more preferably 6% or more and less than 40%, more preferably 6% or more and less than 20%, more preferably 8% or more and less than 18%, and more preferably 9.5% or more and less than 17%.
[0043] The surface of the copper foil substrate of the surface-treated copper foil of the present invention having the surface treatment coating is preferably a glossy surface. By roughening a smooth surface such as a glossy surface, it is easy to form roughened particles of a desired shape at low cost. It should be noted that the glossy surface refers to the surface on the drum-shaped cathode side of the electrolytic copper foil, which is the S surface of the electrolytic copper foil. The copper foil substrate is preferably an electrolytic copper foil, and the surface treatment coating is preferably formed on the glossy surface of the electrolytic copper foil.
[0044] Reference Figure 3 , describing a method for manufacturing an electrolytic copper foil. Figure 3It is a schematic diagram of a manufacturing device for electrolytic copper foil. The electrode is composed of a drum-shaped cathode 1 containing titanium or stainless steel, and an insoluble anode 2 such as an electrode covered with a precious metal oxide, a lead electrode, etc., which is concentrically opposed. Between the two electrodes, a copper sulfate electrolyte 3 flows from the lower part of the device, and an electric current is applied, thereby precipitating a copper plating layer on the surface of the drum-shaped cathode. The drum-shaped cathode 1 rotates at a specified speed, and the precipitated copper plating layer is continuously peeled off and wound up from the surface of the drum-shaped cathode as an electrolytic copper foil 6. The drum-shaped cathode side of the electrolytic copper foil is called the glossy side, and is also called the S (bright) side 5. The reason is that the drum-shaped cathode surface forms a smooth and glossy surface, and the surface of the electrolytic copper foil precipitated and peeled on this surface also forms a smooth and glossy surface. The opposite side of the S surface is called the M (matte) surface 4. It should be noted that the thickness of the electrolytic copper foil used in the surface-treated copper foil of the present invention is preferably 6 to 210 μm.
[0045] The Y value in the XYZ chromaticity system (CIE1931 standard chromaticity system) of TD measured according to JIS Z 8781 of the surface of the surface treated film of the surface treated copper foil of the present invention is preferably 10% or more and 45% or less. If the Y value is 10% or more, it can be considered that the roughened particles are sufficiently small, it is more difficult for powder to fall, and the transmission loss in the high frequency band is further improved. If the Y value is 45% or less, it can be considered that the dendritic precipitation that extends in a direction with a large angle relative to the direction perpendicular to the copper foil substrate and has an effect on the anchoring effect is sufficient, and the normal adhesion and heat-resistant adhesion of the surface treated copper foil to the resin substrate are further improved. From this point of view, the Y value is more preferably 12% or more and 40% or less, more preferably 18% or more and 28% or less, and more preferably 19% or more and 26% or less.
[0046] The surface of the surface treated film of the surface treated copper foil of the present invention has a color mixing ratio (x value) of the X value in the XYZ colorimetric system (CIE1931 standard colorimetric system) of TD measured according to JIS Z 8781, which is preferably 0.38 to 0.50. If the color mixing ratio (x value) of the X value is 0.38 or more, it can be considered that the dendritic precipitation that extends obliquely in the direction with a large angle relative to the direction perpendicular to the copper foil substrate and has an impact on the anchoring effect is sufficient, and the heat-resistant adhesion of the surface treated copper foil to the resin substrate is further improved. If the color mixing ratio (x value) of the X value is 0.50 or less, it can be considered that the dendritic precipitation from the root of the roughened particles is moderate, it is more difficult for powder to fall, and the transmission loss in the high-frequency band is further improved. From this point of view, the color mixing ratio (x value) of the X value is more preferably 0.40 to 0.48, and more preferably 0.41 to 0.47.
[0047] The surface of the surface treated film in the surface treated copper foil of the present invention has a color mixing ratio (y value) of the Y value in the XYZ colorimetric system (CIE1931 standard colorimetric system) of TD measured according to JIS Z 8781, which is preferably 0.32 to 0.36. If the color mixing ratio (y value) of the Y value is 0.32 or more, it can be considered that the dendritic precipitation from the roots of the roughened particles is moderate, it is more difficult for powder to fall, and the transmission loss in the high frequency band is further improved. If the color mixing ratio (y value) of the Y value is 0.36 or less, it can be considered that the dendritic precipitation that extends obliquely in the direction with a large angle relative to the direction perpendicular to the copper foil substrate and has an impact on the anchoring effect is sufficient, and the heat-resistant adhesion of the surface treated copper foil to the resin substrate is further improved. From this point of view, the color mixing ratio (y value) of the Y value is more preferably 0.33 to 0.35, and more preferably 0.34 to 0.35.
[0048] The ten-point average roughness Rzjis value of the surface of the surface-treated film in the surface-treated copper foil of the present invention measured in accordance with JIS B 0601 is preferably 0.8 μm or more and 4.5 μm or less. If the ten-point average roughness Rzjis value is 0.8 μm or more, the productivity of the surface-treated copper foil is improved. If the ten-point average roughness Rzjis value is 4.5 μm or less, the excessive unevenness of the surface that is more macroscopic than the roughened particles is suppressed, so the resistance to powder falling is improved, and the high-frequency characteristics are also improved. From this point of view, the ten-point average roughness Rzjis value is more preferably 1.0 μm or more and 4.3 μm or less, more preferably 1.5 μm or more and 4.0 μm or less, more preferably 1.8 μm or more and 3.8 μm or less, and more preferably 2.0 μm or more and 3.5 μm or less.
[0049] According to the surface treated copper foil of the present invention, powder falling is suppressed, and user operability is excellent. In addition, by using the surface treated copper foil in the conductor loop of the printed wiring board, especially the outer layer, it is possible to obtain an excellent printed wiring board that can achieve both high adhesion and low transmission loss when transmitting high-frequency signals of 1 to 10 GHz, and also ensure the adhesion between the copper foil and the resin substrate (resin layer) at high temperature (260° C.×20 minutes).
[0050] <Method for producing surface-treated copper foil>
[0051] Next, an example of a preferred method for producing the surface-treated copper foil of the present invention will be described. In the present invention, it is preferred that the surface of the copper foil substrate be subjected to a roughening treatment for forming roughened particles.
[0052] (Copper foil substrate)
[0053] As the copper foil substrate, it is preferred to use an electrolytic copper foil or a rolled copper foil having a smooth and glossy surface without coarse irregularities. Among them, from the perspective of productivity and cost, it is preferred to use the S (bright) surface of the electrolytic copper foil, and it is preferred to perform a roughening treatment described later on the S surface. In order to obtain an S surface shape suitable for forming roughened particles, it is preferred to polish the drum-shaped cathode surface used in the manufacture of the electrolytic copper foil with a polishing wheel of No. 1500 to No. 2500.
[0054] (Roughening treatment)
[0055] The roughening treatment forms a roughening treatment layer. The roughening treatment includes the following roughening plating treatment (1) and fixing plating treatment (2).
[0056] Roughening plating treatment (1)
[0057] Roughening plating treatment (1) is a treatment for forming roughening particles on at least one surface of a copper foil substrate. Specifically, the plating treatment is carried out in a copper sulfate bath. In the copper sulfate bath (roughening plating solution basic bath), in order to prevent the roughening particles from falling off, i.e., "powder falling off", additives known to the public such as molybdenum (Mo), arsenic (As), antimony (Sb), bismuth (Bi), selenium (Se), tellurium (Te), and tungsten (W) can be added, and molybdenum (Mo) is particularly preferred. As a result of in-depth research conducted by the inventors, it was found that the following factors have an impact on the surface properties of the surface-treated copper foil. By setting these conditions ingeniously, the effects of the present invention, i.e., high-frequency characteristics, adhesion (normal adhesion and heat-resistant adhesion) and the required characteristics of resistance to powder falling off, can be met at a high level.
[0058] The copper concentration of the copper sulfate bath in the roughening plating treatment (1) is preferably set to 10 to 30 g / L. If the copper concentration of the copper sulfate bath is 10 to 30 g / L, the 20-degree specular gloss Gs(20°) of the surface of the surface-treated film of the surface-treated copper foil can be set to less than 0.8%, the 60-degree specular gloss Gs(60°) of the TD can be set to 0.4% or more, and the specular gloss ratio of the 45-degree specular gloss Gs(45°) of the TD to the 75-degree specular gloss Gs(75°) (Gs(45°) / Gs(75°)) can be set to 0.1 or more and 1.5 or less.
[0059] For the additive added in the copper sulfate bath, molybdenum (Mo) can be cited as an example for explanation. The concentration of molybdenum (Mo) is preferably set to 50 to 300 mg / L. If the concentration of molybdenum (Mo) is 50 to 300 mg / L, the 20-degree specular gloss Gs (20°) of TD on the surface of the surface-treated coating of the surface-treated copper foil can be set to less than 0.8%, the 60-degree specular gloss Gs (60°) of TD can be set to more than 0.4%, and the specular gloss ratio (Gs (45°) / Gs (75°)) of the 45-degree specular gloss Gs (45°) of TD relative to the 75-degree specular gloss Gs (75°) can be set to 0.1 or more and 1.5 or less.
[0060] Next, the electrolysis conditions and the like of the roughening plating treatment (1) will be described.
[0061] In the present invention, the method of the plating treatment is preferably a reel-to-reel plating treatment from the viewpoint of mass production and production cost, for example.
[0062] The processing speed in the roll-to-roll method is related to the surface shape of the roughened layer to be formed, and is preferably set to 10 to 20 m / min. If the processing speed is 10 to 20 m / min, the 20-degree specular gloss Gs(20°) of TD in the surface of the surface-treated coating of the surface-treated copper foil can be set to less than 0.8%, the 60-degree specular gloss Gs(60°) of TD can be set to 0.4% or more, and the specular gloss ratio of the 45-degree specular gloss Gs(45°) of TD to the 75-degree specular gloss Gs(75°) (Gs(45°) / Gs(75°)) can be set to 0.1 or more and 1.5 or less. In addition, in relation to the 85-degree mirror gloss Gs(85°) of TD, for example, by setting the processing speed to 10 to 18 m / min, the 85-degree mirror gloss Gs(85°) of TD can be set to be greater than 4% and less than 50%, and by further setting the processing speed to 12 to 17 m / min, Gs(85°) can be set to be greater than 6% and less than 40%.
[0063] The conditions of the plating treatment can be appropriately adjusted according to the treatment method. In particular, from the viewpoint of suppressing the diffusion of copper ions, it is preferable to set the conditions that are difficult to cause stirring of the plating solution. Therefore, in the roll-to-roll method, it is preferable to make the treatment direction (the direction of the treatment speed) and the direction of the flow of the plating solution between the electrodes (the direction of the inter-electrode flow rate) consistent. In addition, in methods other than the roll-to-roll method, it is desired to treat in a static bath state, and it is preferable not to stir during the plating treatment.
[0064] However, in both the roll-to-roll method and other methods, gas tends to be generated during the plating process, and there is a possibility that agitation may occur due to the buoyancy of the generated gas.
[0065] For example, in the case of a plating process other than a roll-to-roll process such as a batch process, the process of the present invention is completed in a very short time of about several seconds even if it is long, so there is no need to particularly consider agitation due to such gas generation.
[0066] However, in the case of the roll-to-roll method, since it is a continuous treatment, gas is continuously generated in the treatment tank, and the continuously generated gas is constantly floating, so the flow of the plating solution occurs in the floating direction. In addition, in the case of the roll-to-roll method, the copper foil substrate is continuously supplied to the plating solution, so the flow of the plating solution occurs in the conveying direction of the copper foil substrate. When the two flows are consistent, there is almost no need to consider the generation of the above-mentioned gas. However, when the two flows are opposite to each other, unnecessary stirring force is generated on the treated surface, and there is a risk of promoting the diffusion of copper ions. Therefore, when the plating treatment is performed by the roll-to-roll method, it is preferred to select a reaction tank for the plating treatment so that the floating direction of the gas is consistent with the conveying direction of the copper foil substrate (the processing direction of the plating treatment).
[0067] In the roughening plating treatment (1), when the plating treatment is performed in a roll-to-roll method, the absolute value of the difference between the treatment speed and the inter-electrode flow rate of the plating solution flowing along the treatment direction (hereinafter referred to as "treatment direction inter-electrode flow rate") is preferably set to less than 1 m / min. If the absolute value of the difference between the treatment speed and the treatment direction inter-electrode flow rate is less than 1 m / min, it is easy to set the 20-degree specular gloss Gs(20°) of the surface of the surface treated film of the surface treated copper foil to less than 0.8%, the 60-degree specular gloss Gs(60°) of the TD to 0.4% or more, and the specular gloss ratio of the 45-degree specular gloss Gs(45°) of the TD to the 75-degree specular gloss Gs(75°) (Gs(45°) / Gs(75°)) to 0.1 or more and 1.5 or less.
[0068] In the roughening plating treatment (1), it is preferred to perform the plating treatment while gradually decreasing the current density from high to low. In particular, it is preferred to perform the plating treatment while decreasing the current density from high to medium and low current densities in three stages. The high current density is preferably 50 to 80 A / dm 2 The above current density is preferably 45 to 65 A / dm 2 The above low current density is preferably 20 to 50 A / dm 2 In addition, before the above-mentioned plating treatment, it is preferred to use 4 to 10 A / dm 2The current density is less than 3 seconds for preliminary plating. By pre-covering the surface in the preliminary plating, it is easy to obtain the desired roughened particle shape. By plating at these current densities, there is no excessive growth of dendritic precipitation at the root of the roughened particles, causing powder falling, etc., or the lack of dendritic precipitation, especially the deterioration of heat-resistant adhesion, and the dendritic precipitation grows from the root of the roughened particles to the vertex with a good balance. That is, by performing a roughening plating treatment while reducing the current density in stages as described above, the 20-degree mirror gloss Gs (20°) of the TD on the surface of the surface treated film of the surface treated copper foil can be set to less than 0.8%, the 60-degree mirror gloss Gs (60°) of the TD is set to more than 0.4%, and the mirror gloss ratio (Gs (45°) / Gs (75°)) of the 45-degree mirror gloss Gs (45°) of the TD relative to the 75-degree mirror gloss Gs (75°) is set to 0.1 or more and 1.5 or less.
[0069] Current density (A / dm 2 The product of ) and the treatment time (seconds) is preferably high current density treatment (=S 1 ) is set to 20~200{(A / dm 2 )·seconds}, medium current density treatment (=S 2 ) is set to 20~200{(A / dm 2 )·seconds}, low current density treatment (=S 3 ) is set to 20~200{(A / dm 2 )·seconds}, and then the total of all the processing in the three stages (=S T ) is set to 170~270{(A / dm 2 )·seconds}. If the above product is set within the specified range, the 20-degree mirror gloss Gs(20°) of TD on the surface of the surface-treated coating of the surface-treated copper foil can be set to less than 0.8%, the 60-degree mirror gloss Gs(60°) of TD can be set to more than 0.4%, and the mirror gloss ratio of the 45-degree mirror gloss Gs(45°) of TD to the 75-degree mirror gloss Gs(75°) (Gs(45°) / Gs(75°)) can be set to more than 0.1 and less than 1.5.
[0070] Fixed plating treatment (2)
[0071] The fixing plating treatment (2) is a treatment for performing cover plating on the copper foil substrate surface-treated in the above-mentioned roughening plating treatment (1). Thus, the shape of the roughening particles formed in the roughening plating treatment (1) can be maintained.
[0072] The fixed plating treatment in the present invention uses a copper sulfate bath having the same composition as the roughening plating treatment and is performed at the same bath temperature. The composition and bath temperature of the copper sulfate bath will be described in detail later.
[0073] Generally, plating solutions of different compositions are used in the roughening plating process and the fixing plating process. In the fixing plating process, a plating solution with a higher copper concentration and a higher bath temperature than the roughening plating process is used for smoothing, rather than baking plating like the roughening plating process.
[0074] On the other hand, in the present invention, in the fixed plating treatment, the same copper sulfate bath as the roughening plating treatment is also used, and the plating treatment is performed at the same bath temperature. Thus, while the sufficiently roughened particles are fixed to prevent the powder from falling, the surface shape of the roughened particles will not be excessively smoothed, so a roughened surface with a complex concave-convex surface shape is formed. That is, by using a copper sulfate bath with the same composition as the roughening plating treatment, the fixed plating treatment is performed at the same bath temperature, and the 20-degree specular gloss Gs (20°) of the TD on the surface of the surface treated film of the surface treated copper foil can be set to less than 0.8%, the 60-degree specular gloss Gs (60°) of TD can be set to more than 0.4%, and the specular gloss ratio (Gs (45°) / Gs (75°)) of the 45-degree specular gloss Gs (45°) of TD relative to the 75-degree specular gloss Gs (75°) can be set to more than 0.1 and less than 1.5.
[0075] The electrolytic conditions and the like of the fixed plating treatment (2) will be described.
[0076] The plating treatment method is preferably a roll-to-roll plating treatment from the viewpoint of mass production and production cost. In the case of a fixed plating treatment in a roll-to-roll manner, the absolute value of the difference between the treatment speed and the inter-electrode flow rate is preferably set to 6 to 15 m / min. If the absolute value of the difference between the treatment speed and the inter-electrode flow rate is 6 to 15 m / min, the 20-degree mirror gloss Gs (20°) of the TD in the surface treatment coating surface of the surface-treated copper foil can be set to less than 0.8%, the 60-degree mirror gloss Gs (60°) of the TD can be set to 0.4% or more, and the mirror gloss ratio (Gs (45°) / Gs (75°)) of the 45-degree mirror gloss Gs (45°) of the TD relative to the 75-degree mirror gloss Gs (75°) can be set to 0.1 or more and 1.5 or less. It should be noted that in the fixed plating process, the flow direction of the process speed (processing direction) and the flow direction of the inter-electrode flow speed may not be consistent. When they are opposite to each other, one flow speed is calculated as a negative flow speed relative to the other flow speed.
[0077] In the fixed plating treatment (2), the current density is preferably 3 to 25 A / dm 2By performing the plating treatment at the above-mentioned current density, the 20-degree specular gloss Gs(20°) of TD in the surface of the surface-treated coating of the surface-treated copper foil can be set to less than 0.8%, the 60-degree specular gloss Gs(60°) of TD can be set to more than 0.4%, and the specular gloss ratio of the 45-degree specular gloss Gs(45°) of TD to the 75-degree specular gloss Gs(75°) (Gs(45°) / Gs(75°)) can be set to more than 0.1 and less than 1.5.
[0078] In addition, the product K of the current density and the treatment time of the fixed plating treatment (2) is equal to the product S of the current density and the treatment time of the roughening plating treatment (1). T The ratio [(K / S T )×100](%) is preferably set to 20 to 150%. T )×100] is 20 to 150%, the 20 degree mirror gloss Gs(20°) of TD on the surface of the surface treated coating of the surface treated copper foil can be set to less than 0.8%, the 60 degree mirror gloss Gs(60°) of TD can be set to more than 0.4%, and the mirror gloss ratio of the 45 degree mirror gloss Gs(45°) of TD to the 75 degree mirror gloss Gs(75°) (Gs(45°) / Gs(75°)) can be set to more than 0.1 and less than 1.5.
[0079] The following is an example of the composition and electrolysis conditions of the plating solution for roughening plating treatment and the plating solution for fixing plating treatment. It should be noted that the following conditions are preferred examples, and the type, amount, and electrolysis conditions of the additives can be appropriately changed and adjusted as needed within the range that does not hinder the effect of the present invention.
[0080] <Conditions of Roughening Plating Treatment (1)>
[0081] Composition of plating solution
[0082] Copper sulfate pentahydrate···Converted to copper (atom): 10-30 g / L
[0083] Sulfuric acid···100~250g / L
[0084] Sodium molybdate···converted to molybdenum (atom) 50~300mg / L
[0085] Processing speed: 10-20 m / min
[0086] Inter-electrode flow rate in treatment direction: 5-20.5 m / min
[0087] Pre-plating current density: 4 to 10 A / dm 2
[0088] High current density···50~80A / dm 2
[0089] Medium current density···45~65A / dm 2
[0090] Low current density···20~50A / dm 2
[0091] Pre-plating treatment time: 1.0 to 3.0 seconds
[0092] High current density treatment time: 1.2 to 3.0 seconds Medium current density treatment time: 0.8 to 4.0 seconds
[0093] Low current density treatment time: 0.5 to 2.0 seconds
[0094] Bath temperature: 20~30℃
[0095] <Conditions of Fixed Plating Treatment (2)>
[0096] Composition of plating solution: Same as that of plating solution for roughening plating treatment
[0097] Copper sulfate pentahydrate···Converted to copper (atom): 10-30 g / L
[0098] Sulfuric acid···100~250g / L
[0099] Sodium molybdate···converted to molybdenum (atom) 50~300mg / L
[0100] Processing speed: 5-20 m / min
[0101] Inter-electrode flow rate in treatment direction: 1~30m / min
[0102] Current density···3~25A / dm 2
[0103] Processing time: 1 to 15 seconds
[0104] Bath temperature: Same as the bath temperature of the plating solution for roughening plating, 20 to 30°C
[0105] Furthermore, the surface-treated copper foil of the present invention may further form a silane coupling agent layer on the roughening treatment layer, directly or via an intermediate layer such as a base layer containing nickel (Ni), a heat-resistant treatment layer containing zinc (Zn), and a rust-proof treatment layer containing chromium (Cr). It should be noted that the thickness of the intermediate layer and the silane coupling agent layer is very thin, so it does not affect the particle shape of the roughened particles in the roughened surface of the surface-treated copper foil. The particle shape of the roughened particles in the roughened surface of the surface-treated copper foil is substantially determined by the particle shape of the roughened particles in the surface of the roughening treatment layer corresponding to the roughened surface.
[0106] In addition, as a method for forming a silane coupling agent layer, for example, a method of applying a silane coupling agent solution directly or via an intermediate layer on the concavo-convex surface of the roughening treatment layer of the surface-treated copper foil, and then air-drying (natural drying) or heat-drying can be cited. If the water in the applied coupling agent solution evaporates, a silane coupling agent layer is formed and the effect of the present invention is fully exerted. If the heat drying is performed at 50 to 180° C., it is suitable in promoting the reaction between the silane coupling agent and the copper foil.
[0107] The silane coupling agent layer preferably contains at least one of epoxy silane, amino silane, vinyl silane, methacrylic silane, acrylic silane, styryl silane, urea silane, mercapto silane, thioether silane and isocyanate silane.
[0108] As another embodiment, it is preferred that at least one intermediate layer selected from a base layer containing Ni, a heat-resistant layer containing Zn, and a rust-proof layer containing Cr is provided between the roughening treatment layer and the silane coupling agent layer.
[0109] For example, when copper (Cu) in the copper foil substrate and the roughening layer diffuses toward the resin substrate side, causing copper damage and reducing adhesion, it is preferred to form a base layer containing Ni between the roughening layer and the silane coupling agent layer. The base layer containing Ni is preferably formed of at least one selected from nickel (Ni), nickel (Ni)-phosphorus (P), and nickel (Ni)-zinc (Zn).
[0110] When it is necessary to further improve the heat resistance, it is preferred to form a heat-resistant treatment layer containing Zn. The heat-resistant treatment layer containing Zn is preferably formed of, for example, zinc or an alloy containing zinc, that is, at least one alloy containing zinc selected from zinc (Zn)-tin (Sn), zinc (Zn)-nickel (Ni), zinc (Zn)-cobalt (Co), zinc (Zn)-copper (Cu), zinc (Zn)-chromium (Cr) and zinc (Zn)-vanadium (V).
[0111] When it is necessary to further improve the corrosion resistance, it is preferable to form a rust-proofing layer containing Cr. Examples of the rust-proofing layer include a chromium layer formed by chromium plating and a chromate layer formed by chromate treatment.
[0112] When all three layers of the above-mentioned base layer, heat-resistant treatment layer and rust-proof treatment layer are formed, they are preferably formed in this order on the roughening treatment layer. In addition, only one or two layers may be formed depending on the application and target characteristics.
[0113] 〔Production of surface treated copper foil〕
[0114] The method for producing the surface-treated copper foil of the present invention is summarized below.
[0115] In the present invention, it is preferred to produce a surface-treated copper foil according to the following forming steps (S1) to (S5).
[0116] (S1) Roughening layer formation step
[0117] On the copper foil substrate, a roughening treatment layer including roughening particles having a fine concavo-convex surface is formed by electrolysis.
[0118] (S2) Step of forming a base layer
[0119] On the roughened layer, a base layer containing Ni is formed as necessary.
[0120] (S3) Heat-resistant layer formation step
[0121] A heat-resistant layer containing Zn is formed on the roughening layer or the base layer as necessary.
[0122] (S4) Step of forming an anti-rust treatment layer
[0123] A rust-proofing layer containing Cr is formed as needed on the roughening treatment layer or, as needed, on the base layer and / or the heat-resistant treatment layer formed on the roughening treatment layer.
[0124] (S5) Silane coupling agent layer formation step
[0125] The silane coupling agent layer is formed directly on the roughening treatment layer, or is formed via an intermediate layer formed of at least one of a base layer, a heat-resistant treatment layer, and a rust-proof treatment layer.
[0126] In addition, the surface-treated copper foil of the present invention is suitable for manufacturing a copper-clad laminate for a printed wiring board. Such a copper-clad laminate is suitable for manufacturing a printed wiring board with high adhesion and excellent transmission characteristics in a high-frequency band, and exerts excellent effects. The surface-treated copper foil of the present invention is suitable for use as a high-frequency band printed wiring board used in a high-frequency band (particularly a high-frequency band of 1 to 10 GHz).
[0127] In addition, the surface-treated copper foil of the present invention can be used for printed wiring board copper-clad laminates, which are formed by known methods.For example, printed wiring board copper-clad laminates are manufactured by laminating surface-treated copper foil and resin substrate (insulating substrate) in a manner that the roughening surface (pasting surface) of the surface-treated copper foil is opposite to the resin substrate. Such printed wiring board copper-clad laminates are obtained by bonding the surface (roughening surface) of the above-mentioned surface-treated copper foil with the resin substrate. It should be noted that as an insulating substrate, for example, a flexible resin substrate or a rigid resin substrate can be cited, and the surface-treated copper foil of the present invention is particularly suitable for the combination of rigid resin substrates with transmission characteristics and high adhesion in the high-frequency band required for the outer layer.
[0128] In addition, when manufacturing a copper-clad laminate for a printed wiring board, a surface-treated copper foil having a silane coupling agent layer and an insulating substrate can be manufactured by laminating them by heating and pressing. It should be noted that a copper-clad laminate for a printed wiring board manufactured by applying a silane coupling agent on an insulating substrate and laminating the insulating substrate coated with the silane coupling agent and a surface-treated copper foil having a rust-proofing layer on the outermost surface by heating and pressing also has the same effect as the present invention.
[0129] In addition, the printed wiring board can be formed by a known method using the copper-clad laminate for a printed wiring board. Such a printed wiring board has the copper-clad laminate for a printed wiring board.
[0130] Although the embodiment of the present invention has been described above, the above embodiment is only an example of the present invention. The present invention includes the concept of the present invention and any form included in the claims, and various changes can be made within the scope of the present invention.
[0131] Example
[0132] Hereinafter, the present invention will be described in further detail based on Examples, but the following is an example of the present invention.
[0133] (Manufacturing Example: Preparation of Copper Foil Base)
[0134] As a copper foil substrate used as a base material for roughening treatment, a roll-shaped electrolytic copper foil having a thickness of 18 μm was prepared using the following cathode and anode, using a copper sulfate electrolyte solution with the following composition, and under the following electrolysis conditions.
[0135] <Cathode and Anode>
[0136] Cathode: Titanium rotating drum polished with a #2000 polishing wheel
[0137] Anode: Dimensionally stable anode DSA (registered trademark)
[0138] <Copper sulfate electrolyte composition>
[0139] Copper sulfate pentahydrate: converted to Cu, 80g / L
[0140] H 2 SO 4 :70g / L
[0141] Chlorine concentration: 30mg / L
[0142] (additive)
[0143] Hydroxyethyl cellulose: 5mg / L
[0144] <Electrolysis Conditions>
[0145] Bath temperature: 58°C
[0146] Current density: 50A / dm 2 .
[0147] (Example 1)
[0148] In Example 1, the following steps [1] to [3] were performed to obtain a surface-treated copper foil.
[0149] [1] Formation of roughened layer
[0150] A roughened plating surface was formed on the S surface of the copper foil by electroplating. The roughened plating surface was formed using the following roughening plating solution and the fixed plating solution universal basic bath composition, and the inter-electrode flow rate, current density, and treatment time as shown in Tables 1 and 2. The molybdenum concentration was adjusted by adding an aqueous solution of sodium molybdate dihydrate dissolved in pure water to the basic bath.
[0151] <Basic bath composition and bath temperature common to roughening plating solution and fixed plating solution>
[0152] Copper sulfate pentahydrate: converted to Cu, 25g / L
[0153] H 2 SO 4 :160g / L
[0154] Sodium molybdate dihydrate: converted to Mo, 150 mg / L
[0155] Bath temperature: 26°C.
[0156] Table 1
[0157]
[0158] Table 2
[0159] Table 2
[0160]
[0161] [2] Formation of the metal treatment layer
[0162] Next, on the surface of the roughened treatment layer formed in [1] above, metal plating is performed in the order of Ni, Zn, and Cr under the following conditions to form a metal treatment layer (intermediate layer).
[0163] <Ni plating conditions>
[0164] Ni: 40 g / L
[0165] H 3 BO 3 : 5 g / L
[0166] Bath temperature: 20 °C
[0167] pH: 3.6
[0168] Current density: 0.2 A / dm 2
[0169] Treatment time: 10 seconds
[0170] <Zn plating conditions>
[0171] Zn: 2.5 g / L
[0172] NaOH: 40 g / L
[0173] Bath temperature: 20 °C
[0174] Current density: 0.3 A / dm 2
[0175] Treatment time: 5 seconds
[0176] <Cr plating conditions>
[0177] Cr: 5 g / L
[0178] Bath temperature: 30 °C
[0179] pH: 2.2
[0180] Current density: 5 A / dm 2
[0181] Treatment time: 5 seconds
[0182] [3] Formation of silane coupling agent layer
[0183] Finally, a 0.2 mass % 3-glycidoxypropyltrimethoxysilane aqueous solution was applied on the metal treatment layer (particularly the outermost Cr plating layer) formed in the above [2] and dried at 100° C. to form a silane coupling agent layer.
[0184] (Examples 2 to 12 and Comparative Examples 1 to 5)
[0185] Examples 2 to 12 and Comparative Examples 1 to 5 Surface-treated copper foils were obtained by the same method as in Example 1 except that the roughening layer forming step [1] was as described in Tables 1 and 2 above.
[0186] [evaluate]
[0187] The following property evaluations were performed on the surface-treated copper foils according to the above-described Examples and Comparative Examples.
[0188] The evaluation conditions of each property are as follows. Unless otherwise specified, each measurement was performed at room temperature (20°C ± 5°C).
[0189] [Specular gloss]
[0190] The roughened surface of the surface-treated copper foil was measured using a gloss meter (VG7000 manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS Z 8741: 1997 for the 20-degree specular gloss Gs (20°) of TD, the 45-degree specular gloss Gs (45°) of TD, the 60-degree specular gloss Gs (60°) of TD, the 75-degree specular gloss Gs (75°) of TD, and the 85-degree specular gloss Gs (85°) of TD. The measurement was performed three times in a direction (TD direction) orthogonal to the longitudinal direction (conveying direction, MD direction) of the surface-treated copper foil for each light receiving angle, and all the measured values (N=3) were averaged to be recorded as the specular gloss corresponding to each light receiving angle.
[0191] [Y value, x value and y value of XYZ colorimetric system]
[0192] The roughened surface of the surface-treated copper foil was measured using a lightness meter (manufactured by Suga Test Instruments Co., Ltd., model name: SM Color Computer, model: SM-T45) based on JIS Z 8781 to measure the X value, Y value, and Z value of the XYZ colorimetric system specified in CIE. Then, using these values, the reflectance Y value and the color mixing ratio x value and y value were calculated.
[0193] [Ten-point average roughness]
[0194] The roughened surface of the surface-treated copper foil was measured using a contact-type surface roughness measuring machine (“SUFCODA SE1700” manufactured by Kosaka Laboratory Co., Ltd.) to measure the ten-point average roughness Rzjis (μm) defined in JIS B 0601:2001 in a direction (TD direction) perpendicular to the longitudinal direction (conveying direction, MD direction) of the surface-treated copper foil, that is, the ten-point average roughness Rzjis (μm) in TD.
[0195] [Evaluation of high frequency characteristics]
[0196] As an evaluation of high frequency characteristics, the transmission loss in the high frequency band was measured. The details are described below.
[0197] The roughened surface of the surface treated copper foil is laminated on two surfaces of two polyphenylene ether-based low dielectric constant resin substrates, i.e., MEGTRON6 (thickness 80 μm) made by Panasonic Co., Ltd., and pressed for 2 hours under the conditions of surface pressure 3.5 MPa and 200 ° C to make a two-sided copper-clad laminate. The obtained copper-clad laminate is loop-processed to make a loop substrate for a microstrip line with a transmission path width of 300 μm and a length of 70 mm. In the transmission path of the loop substrate, a network analyzer (Keysight Technologies, "N5247A") is used to transmit high-frequency signals and measure transmission losses. The characteristic impedance is set to 50Ω.
[0198] The smaller the absolute value of the measured value of the transmission loss is, the smaller the transmission loss is, indicating that the high-frequency characteristics are good. The high-frequency characteristics were evaluated based on the following evaluation criteria using the obtained measured values as indicators.
[0199] a: The absolute value of transmission loss at 10GHz is less than 1.8dB
[0200] b: The absolute value of the transmission loss at 10 GHz is 1.8 dB or more and less than 2.0 dB
[0201] c: The absolute value of the transmission loss at 10 GHz is 2.0 dB or more.
[0202] [Evaluation of normal adhesion]
[0203] As evaluation of normal adhesion, a peel test was performed based on JIS C 6481: 1996. The details are described below.
[0204] A copper-clad laminate is prepared by the same method as described in the above-mentioned [Evaluation of High Frequency Characteristics], and the copper foil portion (surface-treated copper foil) of the obtained copper-clad laminate is masked with a 10 mm wide tape. After the copper-clad laminate is etched with copper chloride, the tape is removed to prepare a 10 mm wide loop wiring board. The peel strength of the 10 mm wide loop wiring portion (copper foil portion) of the loop wiring board is measured when it is peeled off from the resin substrate at a speed of 50 mm / min in the 90 degree direction using a Tensilon testing machine manufactured by Toyo Seiki Seisaku-sho Co., Ltd. The obtained measured value is used as an indicator to evaluate the adhesion based on the following evaluation criteria.
[0205] <Evaluation criteria for normal adhesion>
[0206] a: Peel strength is 0.61 kN / m or more
[0207] b: Peel strength is 0.52 kN / m or more and less than 0.61 kN / m
[0208] c: Peel strength is lower than 0.52 kN / m.
[0209] [Evaluation of heat-resistant adhesion]
[0210] As an evaluation of heat-resistant adhesion, a peel test after heat treatment was performed in accordance with JIS C 6481: 1996. The details are described below.
[0211] A copper-clad laminate is made by the same method as described in the above-mentioned [Evaluation of High-Frequency Characteristics], and the copper foil portion of the obtained copper-clad laminate is masked with a 10 mm wide tape. After the copper-clad laminate is etched with copper chloride, the tape is removed to make a 10 mm wide loop wiring board. After the loop wiring board is heated in a heating oven at 260°C for 20 minutes, it is naturally air-cooled to room temperature. Thereafter, a Tensilon testing machine manufactured by Toyo Seiki Seisaku-sho Co., Ltd. is used to measure the peel strength when the 10 mm wide loop wiring portion (copper foil portion) of the loop wiring board is peeled off from the resin substrate at a speed of 50 mm / min in the 90-degree direction. Using the obtained measured value as an indicator, the heat-resistant adhesion is evaluated based on the following evaluation criteria.
[0212] <Evaluation Criteria for Heat-Resistant Adhesion>
[0213] a: Peel strength is 0.52kN / m or more
[0214] b: Peel strength is 0.43 kN / m or more and less than 0.52 kN / m
[0215] c: Peel strength is lower than 0.43 kN / m.
[0216] [Evaluation of Powder Falling Resistance]
[0217] On the roughened surface of the surface-treated copper foil, the back side of the filter paper No. 2 (φ55 mm) (equivalent to type 2 of JIS P 3801) manufactured by ADVANTE Toyo Co., Ltd. was placed as the roughened surface side, and a 250 g weight with a contact surface of φ20 mm was placed in the center. In this state, the filter paper was directly clamped with tweezers, and stretched for 150 mm in the width direction (TD direction) of the surface-treated copper foil at a speed of about 30 mm / sec, and the copper powder attached to the filter paper was visually observed, and the powder drop resistance was evaluated based on the following evaluation criteria.
[0218] <Evaluation Criteria for Powder Fall Resistance>
[0219] a: No copper powder was observed to adhere to the filter paper.
[0220] b: Copper powder was observed to adhere to the filter paper, but the adhesion area of the copper powder was less than 10% of the contact surface (φ20 mm) of the weight.
[0221] c: Copper powder was observed to adhere to the filter paper, but the copper powder adhered to an area of 10% or more of the contact surface (φ20 mm) of the weight.
[0222] [Overall evaluation]
[0223] Comprehensive evaluation was performed based on the following evaluation criteria by taking all of the above-mentioned high frequency characteristics, normal adhesion, heat-resistant adhesion, and powder drop resistance into consideration. It should be noted that in this example, A and B were at a passing level in the comprehensive evaluation.
[0224] <Evaluation Criteria for Comprehensive Evaluation>
[0225] A (excellent): All evaluations are rated A.
[0226] B (Pass): There is no C rating in all the ratings.
[0227] C (Unacceptable): At least one evaluation is C.
[0228] [Table 3]
[0229]
[0230] As shown in Table 3, the 20-degree specular gloss Gs(20°) of the surface treated copper foil of Examples 1 to 12 in TD measured according to JIS Z8741:1997 is less than 0.8%, the 60-degree specular gloss Gs(60°) of the surface treated film surface in TD measured according to JIS Z8741:1997 is 0.4% or more, and the specular gloss ratio of the 45-degree specular gloss Gs(45°) to the 75-degree specular gloss Gs(75°) of the surface treated film surface in TD measured according to JIS Z 8741:1997 (Gs(45°) / Gs(75°)) is controlled to 0.1 to 1.5, so that it is confirmed that the high-frequency characteristics are excellent, and high adhesion (normal adhesion and heat-resistant adhesion) and high resistance to powder falling are exerted.
[0231] In contrast, the results of the surface treated copper foils of Comparative Examples 1 and 4 were that Gs(20°) was as high as 0.8 or more, and the heat-resistant adhesion was poor. The result of Comparative Example 2 was that Gs(60°) was as low as 0.3%, so the high-frequency characteristics were poor. The result of Comparative Example 3 was that Gs(45°) / Gs(75°) was as large as 1.8, so the powder drop resistance was poor. The result of Comparative Example 5 was that Gs(60°) was as low as 0.3%, and Gs(45°) / Gs(75°) was also as large as 1.8, so the high-frequency characteristics and powder drop resistance were poor.
[0232] Description of Reference Numerals
[0233] 1 Cathode
[0234] 2 Insoluble anode
[0235] 3 Copper sulfate electrolyte
[0236] 4 M side
[0237] 5 S-side
[0238] 6 Electrolytic copper foil
Claims
1. A surface-treated copper foil for a printed wiring board, comprising a surface-treated coating on at least one surface of a copper foil substrate, wherein the surface-treated coating comprises a roughening layer having roughening particles formed thereon, The surface of the surface treatment film has a 20 degree specular gloss Gs (20°) of less than 0.8% as measured in accordance with JIS Z 8741:1997. The surface of the surface treatment film has a 60 degree specular gloss Gs (60°) of 0.4% or more measured in accordance with JIS Z 8741:1997. The surface of the surface treatment film has a specular gloss ratio (Gs(45°) / Gs(75°)) of 45° specular gloss Gs(45°) to 75° specular gloss Gs(75°) in TD measured in accordance with JIS Z 8741:1997 of 0.1 to 1.
5.
2. The surface-treated copper foil for a printed wiring board according to claim 1, wherein The surface of the surface treatment film has a TD 85-degree specular gloss Gs (85°) of 4% or more and less than 50% as measured in accordance with JIS Z 8741:1997.
3. The surface-treated copper foil for a printed wiring board according to claim 1, wherein The surface of the copper foil substrate having the surface treatment film is a glossy surface.
4. The surface-treated copper foil for a printed wiring board according to claim 1, wherein The surface of the surface treatment film has a Y value in an XYZ chromaticity system of TD measured in accordance with JIS Z 8781 of 10% to 45%.
5. The surface-treated copper foil for a printed wiring board according to claim 1, wherein The surface of the surface treatment film has a ten-point average roughness Rzjis value measured in accordance with JIS B 0601 of 0.8 μm or more and 4.5 μm or less. 6 . A copper-clad laminate for a printed wiring board, obtained by bonding the surface of the surface-treated copper foil for a printed wiring board according to claim 1 , on which the surface-treated film is formed, to a resin substrate.
7. A printed wiring board comprising the copper-clad laminate for a printed wiring board according to claim 6.
Citation Information
Patent Citations
Toner density detecting device for image forming device
JP1987094862A
Electrolytic copper foil and process for producing electrolytic copper foil, surface treated electrolytic copper foil using said electrolytic copper foil, and copper-clad laminate plate and printed wi
CN101146933A
Flexible printed wiring board for chip-on-film
US20040163842A1